Phasic cholinergic signaling promotes emergence of local gamma rhythms in excitatory–inhibitory networks. (16th May 2020) - Lu, Yiqing; Sarter, Martin; Zochowski, Michal; Booth, Victoria
Abstract: Recent experimental results have shown that the detection of cues in behavioral attention tasks relies on transient increases of acetylcholine (ACh) release in frontal cortex and cholinergically driven oscillatory activity in the gamma frequency band (Howe et al. Journal of Neuroscience, 2017, 37, 3215). The cue‐induced gamma rhythmic activity requires stimulation of M1 muscarinic receptors. Using biophysical computational modeling, we show that a network of excitatory (E) and inhibitory (I) neurons that initially displays asynchronous firing can generate transient gamma oscillatory activity in response to simulated brief pulses of ACh. ACh effects are simulated as transient modulation of the conductance of an M‐type K + current which is blocked by activation of muscarinic receptors and has significant effects on neuronal excitability. The ACh‐induced effects on the M current conductance, g Ks, change network dynamics to promote the emergence of network gamma rhythmicity through a Pyramidal‐Interneuronal Network Gamma mechanism. Depending on connectivity strengths between and among E and I cells, gamma activity decays with the simulated g Ks transient modulation or is sustained in the network after the g Ks transient has completely dissipated. We investigated the sensitivity of the emergent gamma activity to synaptic strengths, external noise and simulated levels of g Ks modulation. To address recent experimental findings that cholinergic signaling is likely spatially focused and dynamic, we show that localized g Ks modulation can induce transient changes of cellular excitability in local subnetworks, subsequently causing population‐specific gamma oscillations. These results highlight dynamical mechanisms underlying localization of ACh‐driven responses and suggest that spatially localized, cholinergically induced gamma may contribute to selectivity in the processing of competing external stimuli, as occurs in attentional tasks. Abstract : Recent experiments showed that cholinergic signaling in the prefrontal cortex is fast and spatially localized in the context of attentional behavioral tasks. The cholinergic transients also generated gamma frequency oscillations that contributed to successful attentional performance. Using computational modeling, we show that transient cholinergic modulation of neural excitability induced the emergence of transient synchronous gamma activity from a background of asynchronous firing in excitatory–inhibitory neural networks.